Evaluation of uterine cavity by hysteroscopic examination in infertile women in BSMMU - Banu, Jesmine; Deeba, Farzana; Fatima, Parveen; Sultana, Parveen (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Hysteroscopy is the gold standard procedure for uterine cavity exploration. However, hysteroscopy is only recommended by the WHO when clinical or complementary exams (ultrasound, HSG) suggest intrauterine abnormality or after in vitro fertilization failure. Nevertheless, many specialists feel that hysteroscopy is a more accurate tool. Objective: The aim of this prospective study is to find out the evaluation of uterine cavity by hysteroscopic examination as a primary workup of infertility. To asses the uterine pathology which is the causal factor for infertility. Method: This is a cross sectional study in which total 100 infertile patients were enrolled from infertility OPD in BSMMU with maintaining inclusion and exclusion criteria Hysteroscopy was performed with a standard sequence. The endocervical canal, uterine cavity, endometrium, and tubal ostia were inspected and findings were recorded. Results: Hysteroscopy was performed in 100 infertile women,among them 44% were presented with primary infertility and 56% presented with secondary infertility. The most common indication for diagnostic hysteroscopy was as a part of an infertility workup 80% cases. Other indication included abnormal hysterosalphingography, recurrent pregnancy loss and unexplained infertility. Hysteroscopy revealed a normal uterine cavity in 51 ( 51 % ) women (Table 2).among them majority of patients were primary infertility.and age less than 30 years. Hysteroscopic abnormalities are significantly high in secondary than primary infertility. Conclusion: In this study abnormal hysteroscopic findings were found in 49% who underwent diagnostic hysteroscopy. Our data are an additional argument to suggest that diagnostic hysteroscopy as part of investigation in infertile woman to evaluate uterine pathology. Routine diagnostic hysteroscopy should be part of an infertility workup in both primary and secondary infertility.At the same setting therapeutic approach also be possible which is beneficial for the patients.